Care of pregnant women with epilepsy in the United Kingdom: A national survey of healthcare professionals. (September 2022) - Taylor, Emily; Junaid, Fatima; Khattak, Hajra; Sheikh, Jameela; Ghosh, Jay; Kemah, Ben-Lawrence; Nelson-Piercy, Catherine; Morley, Kim; Moss, Ngawai; Knox, Ellen; Allotey, John; Thangaratinam, Shakila
Highlights: Current care for pregnant women with epilepsy in the UK is fragmented, with wide variation in when, how and by whom these women are seen. There is a need for standardised, accessible care to prevent morbidity and mortality in pregnant women with epilepsy. Priorities for future research include optimising communication with pregnant women regarding their epilepsy, improving seizure risk prediction and understanding the impact of anti-seizure medications on babies born to women with epilepsy. Abstract: Objectives: To map the care provided to pregnant women with epilepsy in UK maternity units and identify future research priorities by conducting a nationwide survey of healthcare professionals. Study design: A prospective cross-sectional electronic survey was conducted between 29 April and 30 October 2021. The survey included 23 questions developed and refined with relevant stakeholders, including a woman with lived experience of epilepsy and pregnancy. We used descriptive analyses to summarise responses and estimated proportions with medians and interquartile ranges. Results: 144 individual healthcare professionals from 94 hospitals, representing 77 NHS Trusts, participated in the survey. Obstetricians were the most common responders (45%, 65/144) and almost half (47%, 7/15) of regions had a survey response rate per NHS Trust greater than 50%. Six pregnant women with epilepsy, on average, were booked into antenatal care per hospital per month, and 49% (46/94) of hospitals saw women for specialist antenatal care in the first trimester. The care provided across healthcare systems varied, with multiple pathways for referral to specialist care within regions. Midwife referral was the most used care pathway (80%, 75/94). Less than a third of hospitals (31%, 29/94) ran joint obstetric/neurology clinics for pregnant women with epilepsy. Most survey respondents (81%, 117/144) were confident talking to pregnant women about their risk of seizures but only a minority (20%, 29/144) used validated calculators to assess this risk. There was broad agreement across healthcare professionals that the priorities for research should focus on how to improve communication and address pregnant women's concerns regarding epilepsy and pregnancy, and to develop further understanding on the optimal use and long-term effects of anti-seizure medication. Conclusion: Our UK nationwide survey of hospital-based maternity services for pregnant women with epilepsy identified wide variation in when, how and by whom these women are seen, with differences between and within the UK regions. This survey highlights areas for improvement in the care of pregnant women with epilepsy .